Study guides

Q: How do you factor 6x3-x2 plus 17 equals 2x2 plus 47?

Write your answer...

Submit

Related questions

2x2 equals 5

3

2x2+13x+15 = (2x+3)(x+5)

2x2 + 11x + 15 = (x + 3)(2x + 5).

-7

4x4 + 1 = (2x2 - 2x + 1)(2x2 + 2x + 1)

x2 + x2 = 2x2

No.

2x2 + 10 - 9x = 0 or 2x2 - 9x + 10 = 0 So (x - 2)*(2x - 5) = 0

Doesn't factor evenly, use quadratic

2x2=4x4=16

The discriminant is -199.

The discriminant is 25.

(2x + 1)(x + 4)

No. You'd have to use the ABC-formula

X((x+1)^2)

(2x + 1)(x + 3)

(2x+4)(x+1)

22 = 4

The expression cannot be factorised.

x3 + 2x2 - 3x - 6 = (x2 - 3)(x + 2)

2(x + 6)(x + 3)

2(x^2 + 11x + 4)

2(x^2 +2x + 3)

2x2 - 5x + 12 does not factor. 2x2 - 5x - 12 factors into (2x + 3)(x - 4) 2x2 + 5x - 12 factors into (2x - 3)(x + 4)